2021
DOI: 10.1101/2021.01.08.425985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolvability and constraint in the primate basicranium, shoulder, and hip and the importance of multi-trait evolution

Abstract: The scapula shares developmental and functional relationships with traits of the basicranium, vertebral column, humerus, and clavicle. As a limb girdle, it also shares analogous characteristics with the pelvis. Despite these relationships, studies of primate shoulder evolution often focus on traits of the scapula in isolation. Such analyses may lead to spurious conclusions, as they implicitly model the scapula as evolving independent of other anatomical regions. Traits of the shoulder girdle share genetic cova… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 75 publications
2
19
1
Order By: Relevance
“…This result aligns with known developmental and functional relationships among these anatomical regions. Overall, Agosto and Auerbach (2021) demonstrated that the evolution of the primate shoulder is more complex than previously perceived, uncovering evolutionary covariance with anatomical regions once assumed to be independent of the shoulder (i.e., the basicranium). These relationships, however, are not evident when evaluating the scapula or its traits alone.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…This result aligns with known developmental and functional relationships among these anatomical regions. Overall, Agosto and Auerbach (2021) demonstrated that the evolution of the primate shoulder is more complex than previously perceived, uncovering evolutionary covariance with anatomical regions once assumed to be independent of the shoulder (i.e., the basicranium). These relationships, however, are not evident when evaluating the scapula or its traits alone.…”
Section: Introductionmentioning
confidence: 85%
“…We expect that there will be evidence that, especially for the basicranium, shoulder, and pelvis, relationships with each other will lead to constraints in the evolutionary potential of the traits within each anatomical region, following the results of Agosto and Auerbach (2021).…”
Section: Study Predictionsmentioning
confidence: 97%
See 2 more Smart Citations
“…This assumes that the estimated P or G from the extant population is similar enough to G in the ancestral, extinct population. Based on similarities between closely related extant species, a wide array of work (both neontological and paleontological) has assumed that P (or G ) from an extant population is representative of the ancestral G , which has allowed researchers to make evolutionary inferences from phenotypic data across macroevolutionary timescales in ways that would otherwise be impossible (Ackermann and Cheverud 2004; de Oliveira et al 2009; Rolian 2009; Marroig and Cheverud 2010; Young et al 2010; Grabowski et al 2011; Grabowski 2013; Baab 2018; Villamil 2018; Savell 2020; Agosto and Auerbach 2021).…”
Section: Quantitative Genetics In the Rock Recordmentioning
confidence: 99%